2022
DOI: 10.3390/cells11040677
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Poly(A) Tail Processing in Repeat Expansion Diseases

Abstract: Repeat expansion diseases are a group of more than 40 disorders that affect mainly the nervous and/or muscular system and include myotonic dystrophies, Huntington’s disease, and fragile X syndrome. The mutation-driven expanded repeat tract occurs in specific genes and is composed of tri- to dodeca-nucleotide-long units. Mutant mRNA is a pathogenic factor or important contributor to the disease and has great potential as a therapeutic target. Although repeat expansion diseases are quite well known, there are li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 156 publications
(207 reference statements)
0
3
0
Order By: Relevance
“…The exact role of mutant transcripts in pathogenic mechanisms in polyQ diseases is being unraveled [10][11][12][13]. RNA-related studies have demonstrated so far: incomplete splicing of HTT mRNA [14], abnormal interactions of RNAs containing expanded CAG repeats with proteins [15,16], and RNA foci formation [17,18], and potential importance of alternative polyadenylation of various polyQ transcripts [19]. Furthermore, mutant polyQ disease transcripts have been shown to be promising therapeutic targets in strategies that aim to downregulate mutant gene expression [2,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of mutant transcripts in pathogenic mechanisms in polyQ diseases is being unraveled [10][11][12][13]. RNA-related studies have demonstrated so far: incomplete splicing of HTT mRNA [14], abnormal interactions of RNAs containing expanded CAG repeats with proteins [15,16], and RNA foci formation [17,18], and potential importance of alternative polyadenylation of various polyQ transcripts [19]. Furthermore, mutant polyQ disease transcripts have been shown to be promising therapeutic targets in strategies that aim to downregulate mutant gene expression [2,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is rather a complicated network of effects of nuclear inclusions, mutant atrophin‐1 gain of function mechanisms resulting from increase in the number of its interactions, and transcription deregulation. There are other molecular mechanisms, already studied for other polyQ diseases, like RAN translation, 118,119 splicing deregulation, 120 or alternative polyadenylation 121 that should also be considered in the context of DRPLA.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Investigating mRNAs from genes implicated either in HD or spinocerebellar ataxia type 3 (SCA3) provides information about disproportions in allelic expression, as well as changes in expression levels during neuronal differentiation. This is a starting point for detailed analyses of mutant mRNA-specific processes (Ciesiolka et al, 2021 ; Joachimiak et al, 2022 ), which are important for a precise description of molecular mechanisms underlying polyQ diseases. In the last short talk in this session, Sambhavi Puri (Boston University School of Medicine, Boston, USA) shared the results on circRNAs deregulation in AD.…”
Section: Introductionmentioning
confidence: 99%